Role of digital technology in delivering 'healthy futures' and 'healthy cities'. Issue 11 (20th November 2020) - Makeham, Meredith
Abstract: Digital health technologies and services play a critical role in the delivery of safe and efficient healthcare and better health outcomes. Interoperability of these technologies and services, as well as digital inclusion for communities are important enablers of a modern, connected health system. The ongoing development of these factors is an aspiration of Australia's National Digital Health Strategy (NDHS). The Australian Digital Health Agency co‐designed the NDHS with input from healthcare consumers and providers, digital health industry, academic and policy experts and organisations. Approved by all Australian governments in 2017, it provides a forward vision to 2022, with seven pillars that include: Access to health information through My Health record; Secure Messaging; Medicines Safety; Interoperability; Enhanced models of care; Workforce and Education and Driving Innovation. All of these pillars have interdependent features, and many play a role in enabling communities to live healthier and happier lives supported by better connected healthcare services as well as access to information in a timely and efficient manner at the point of care. A 'Communities of Excellence' programme has supported regional communities to connect health services to My Health Record, increase digital health tools use and provide digital health literacy support to consumers. The aims of this programme are to allow the benefits of improved interoperability and better connected care to flow to people and their clinicians, test innovation that could go on to be scaled nationally, and close the health inequity gap experienced by people in rural and remote communities.